The present, past, and future of labor-saving technologies - Jacopo Staccioli; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
The present chapter provides a historical reappraisal of labor-saving technologies. It reviews and systematizes theoretical contributions and empirical findings documenting the presence of labor- and time-saving heuristics in innovative efforts back since the First Industrial Revolution. More in detail, with the help of various patent analyses, the chapter documents the presence of labor-saving heuristics in the latest wave of technological innovation, detecting the human functions substituted by the underlying technologies. Against a reductionist approach conceiving robots as the only threat for labor displacement, it shall be argued that labor-saving technologies consist of a complex and heterogeneous bundle of innovations uncovering a much wider set of artifacts and functions. Motivated by the recurrent debate on the threats of automation occurring in the last couple of centuries, evidence is provided on the existence of long waves and clusters in relevant innovations, discussing how the overall cluster of labor-saving technologies consists of heterogeneous and often independent innovations following remarkably different time-trajectories. The chapter closes with an outline of potential future trends in labor-saving technologies and room for policy actions.
Keywords: O3; C38; J24; 330; Human-Machine Relationship; History of Technology; Labor-Saving Heuristics